ANALISIS MAKNA KONOTASI DALAM LIRIK LAGU “SAMPAI JADI DEBU” KARYA ANANDA BADUDU - Achmad Yuhdi; Feni Amanda Putri (FKIP, Universitas Palangka Raya, 2023)
The purpose of this research is to analyze the connotative meaning of the lyrics of the song “Sampai Jadi Debu” by Ananda Badudu. The research used is qualitative research with descriptive methods. The data in this study is the meaning contained in a song. Data collection techniques were carried out by reading, observing, and taking notes. The instrument used is documentation. The results of the study show that the lyrics of the song “Sampai Jadi Debu” by Ananda Badudu contain connotative meanings related to eternal and eternal love. Through the use of strong and symbolic words and phrases, the verses of the song depict a very strong promise of loyalty and trust in a relationship.